Availability and Use of Intermediate Sanctions by Judges and Corrections Professionals in the United States, 1994 - Corrothers, Helen G. ([Verlag nicht ermittelbar], 1998)
This survey is part of a larger project designed to explore ways to increase the availability and use of intermediate sanctions (IS) on a national level without jeopardizing public safety. A model for an Intermediate Punishment System is suggested. The survey was undertaken to ascertain attitudes and practices concerning IS for three groups: state and federal judges (Part 3), correctional system administrators responsible for community corrections in their state or jurisdiction (Part 1), and program directors who actually operated community programs (Part 2). The units of analysis were intermediate sanctions/programs operating in jurisdictions across the United States. Data were collected on the availability and frequency of use of IS, as well as costs, client/staffing ratios, use of rehabilitative programming, respondents' opinions concerning the field's needs, and program eligibility criteria. Information was also gathered on how decisions were made to place offenders into the various programs, program outcome and whether the program was viewed as being successful (and how this was measured), and types of new programs needed.